Adaptive Blood Cell Variability in the Annual Life Cycle of the Ground Squirrel Urocitellus undulatus - Teplova, P. O.; Komelina, N. P.; Yegorov, A. Ye; Lizorkina, K. I.; Zakharova, N. M. (Journal of evolutionary biochemistry and physiology, 2024)
The complete blood count (CBC) dynamics was investigated in long-tailed ground squirrels Urocitellus undulatus ( n = 100) during different periods of their annual activity. While blood cell (WBC), platelet (PLT), and red blood cell (RBC) counts were determined in summer (normothermia, June–July), fall (preparatory period, October), winter torpor (hypothermia, December–February) and winter active (euthermia, interbout arousals, December–February) periods. In fall, PLT and WBC counts increased by ~40% compared to summer. Under winter torpor, thrombocytosis and leukocytosis were replaced by extreme thrombocytopenia (↓ ~90%), as well as leukopenia in all WBC subpopulations (↓ ~80%). During brief interbout arousals, PLT and WBC counts reached the summer values except for a slightly increased MPV (mean platelet volume). As fall approached, there was an insignificant erythrocytosis (↑ ~10%), which together with changes in other indices could have suggested a mild fall-time hypoxia. During winter torpid and euthermic periods, RBC counts were almost indistinguishable from the summer control values, however, atypical RBC forms occurred both in the fall preparatory period and during hibernation itself. The results are discussed in the context of blood cell adaptation to harsh conditions of hibernation in ground squirrels, and can be useful in studying the adaptive abilities of homoeotherms, including humans.